2016
DOI: 10.4088/jcp.15m10358
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Antisocial Behavioral Syndromes in Adulthood

Abstract: Objective To present current, nationally representative U.S. findings on prevalence, correlates, psychiatric comorbidity, disability and treatment of DSM-5 antisocial personality disorder (ASPD) and syndromal adult antisocial behavior without conduct disorder before age 15 (AABS). Method Face-to-face interviews with respondents (n=36,309) in the 2012-2013 National Epidemiologic Survey on Alcohol and Related Conditions–III. DSM-5 alcohol, nicotine, specific drug use disorders, and selected mood, anxiety, trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 57 publications
2
21
0
2
Order By: Relevance
“…Participants receiving a PD diagnosis in our sample were more likely to be women, white British, and from lower SES groups, consistent with the previous literature [24,27,39,40]. While PD diagnoses were more likely to be recorded for people of white British ethnicity accepted into EIP care for suspected psychosis, our study does not provide information on the relative prevalence of PD by ethnicity in the general population.…”
Section: Meaning Of Findingssupporting
confidence: 83%
“…Participants receiving a PD diagnosis in our sample were more likely to be women, white British, and from lower SES groups, consistent with the previous literature [24,27,39,40]. While PD diagnoses were more likely to be recorded for people of white British ethnicity accepted into EIP care for suspected psychosis, our study does not provide information on the relative prevalence of PD by ethnicity in the general population.…”
Section: Meaning Of Findingssupporting
confidence: 83%
“…Sex differences existed, to some extent, in our study. Our ASPD cases included about two-thirds males, which is typical [ 1 ]. The base model with only sex and age showed that sex is a significant predictor of ASPD, however, the AUC value was quite low, indicating that sex accounts only for a small portion of the variance in ASPD.…”
Section: Discussionmentioning
confidence: 99%
“…18 Adults who demonstrate antisocial behaviors may experience many difficulties in developing and maintaining positive relationships, have trouble sustaining successful employment, and have problems with the law, among other challenges. 19 , 20 , 21 Antisocial behaviors are generally found to be more prevalent among men compared with women, again making the examination of sex differences an important consideration. 22 , 23 , 24 Harsh physical punishment and child maltreatment are likely associated with antisocial behaviors among men and women in the general population in the United States—the extent, however, is unknown.…”
Section: Introductionmentioning
confidence: 99%